Sperm as an indicator of reproductive risk among petroleum refinery workers. Issue 2 (February 1985) - Rosenberg, M J; Wyrobek, A J; Ratcliffe, J; Gordon, L A; Watchmaker, G; Fox, S H; Moore, D H; Hornung, R W
Abstract : A questionnaire study of men in a wastewater treatment plant of a petroleum refinery showed twice the rate of fetal loss in the period during employment in the plant compared with the periods before and after. Questions regarding the interpretation of that study and continuing concern about reproductive risk prompted us to perform a cross sectional evaluation of sperm concentration and morphology. After adjustment for an abstinence period, the mean sperm concentration of the 74 unexposed men did not differ significantly from that of the 34 exposed men (79.9 million/cm3 v 68.2 million/cm3, p(1) = 0.16). The two groups also had a similar proportion of sperm with abnormal morphology (49.1% v 44.5%, p(1) = 0.94). This lack of association remained when degree of exposure, age, use of alcohol and marijuana, past illness or fever, use of baths or sauna, and history of urological problems were considered. These results are most consistent with the absence of sperm mediated reproductive problems.